Association of Duration of Preoperative Opioid Use with Reoperation After One-level Anterior Cervical Discectomy and Fusion in Nonmyelopathic Patients. Issue 13 (1st July 2021) - Samuel, Andre M.; Lovecchio, Francis C.; Premkumar, Ajay; Vaishnav, Avani S.; Kim, Han Jo; Qureshi, Sheeraz A.
Abstract : Study Design: Retrospective cohort study. Objective: The aim of this study was to determine that rates of preoperative opioid use in patients undergoing single-level anterior discectomy and fusion (ACDF) without myelopathy and determine the association with reoperations over 5 years Summary of Background Data: Preoperative opioid use before cervical spine surgery has been linked to worse postoperative outcomes. However, no studies have determined the association of duration and type of opioid used with reoperations after ACDF. Methods: Patients undergoing single-level ACDF without myelopathy between 2007 and 2016 with at least 5-year follow-up were identified in one private insurance administrative database. Preoperative opiate use was divided into acute (within 3 months), subacute (acute use and use between 3 and 6 months), and chronic (subacute use and use before 6 months) and by the opiate medication prescribed (tramadol, oxycodone, and hydrocodone). Postoperative rates of additional cervical spine surgery were determined at 5 years and multivariate logistic regression was used to determine the association of preoperative opiates with additional surgery. Results: Of 445 patients undergoing single-level ACDF without myelopathy, 66.3% were taking opioid medications before surgery. The most commonly used preoperative opioid was hydrocodone (50.3% acute use, 24.7% chronic use). Opioid-naïve patients had a 5-year reoperation rate of 4.7%, compared to 25.0%, 15.5%, and 23.3% with chronic preoperative use of tramadol, hydrocodone, and oxycodone. In multivariate analysis, controlling for age, sex, and Charlson Comorbidity Index, chronic use of hydrocodone (odds ratio [OR] = 2.08, P = 0.05), oxycodone (OR = 4.46, P < 0.01), and tramadol (OR = 4.01, P = 0.01) were all associated with increased reoperations. However, acute use of hydrocodone, oxycodone, and tramadol was not associated with reoperations ( P > 0.05). Conclusion: Both subacute and chronic use of common lower-dose opioid medications is associated with increased reoperations after single-level ACDF in nonmyelopathic patients. This information is critical when counseling patients preoperatively and developing preoperative opioid cessation programs. Level of Evidence: 3 Abstract : In 445 patients undergoing single-level anterior discectomy and fusion without myelopathy, 66.3% were taking opioid medications before surgery. Chronic preoperative use of hydrocodone, oxycodone, and tramadol were all independently associated with increased reoperations, while acute preoperative was not associated with reoperations.